Multidimensional Recurrence Quantification Analysis (MdRQA) for the Analysis of Multidimensional Time-Series: A Software Implementation in MATLAB and Its Application to Group-Level Data in Joint Action - Wallot, Sebastian; Roepstorff, Andreas; Mønster, Dan (Frontiers in Psychology, 2016)
We introduce Multidimensional Recurrence Quantification Analysis (MdRQA) as a tool to analyze multidimensional time-series data. We show how MdRQA can be used to capture the dynamics of high-dimensional signals, and how MdRQA can be used to assess coupling between two or more variables. In particular, we describe applications of the method in research on joint and collective action, as it provides a coherent analysis framework to systematically investigate dynamics at different group levels – from individual dynamics, to dyadic dynamics, up to global group-level of arbitrary size. The appendix contains a software implementation in MATLAB to calculate MdRQA measures.